Clinic Blood Pressure Underestimates Ambulatory Blood Pressure in an Untreated Employer-Based US Population: Results From the Masked Hypertension Study. Issue 23 (6th December 2016) - Schwartz, Joseph E.; Burg, Matthew M.; Shimbo, Daichi; Broderick, Joan E.; Stone, Arthur A.; Ishikawa, Joji; Sloan, Richard; Yurgel, Tyla; Grossman, Steven; Pickering, Thomas G.
Abstract : Background: Ambulatory blood pressure (ABP) is consistently superior to clinic blood pressure (CBP) as a predictor of cardiovascular morbidity and mortality risk. A common perception is that ABP is usually lower than CBP. The relationship of the CBP minus ABP difference to age has not been examined in the United States. Methods: Between 2005 and 2012, 888 healthy, employed, middle-aged (mean±SD age, 45±10.4 years) individuals (59% female, 7.4% black, 12% Hispanic) with screening BP <160/105 mm Hg and not taking antihypertensive medication completed 3 separate clinic BP assessments and a 24-hour ABP recording for the Masked Hypertension Study. The distributions of CBP, mean awake ABP (aABP), and the CBP−aABP difference in the full sample and by demographic characteristics were compared. Locally weighted scatterplot smoothing was used to model the relationship of the BP measures to age and body mass index. The prevalence of discrepancies in ABP- versus CBP-defined hypertension status—white-coat hypertension and masked hypertension—were also examined. Results: Average systolic/diastolic aABP (123.0/77.4±10.3/7.4 mm Hg) was significantly higher than the average of 9 CBP readings over 3 visits (116.0/75.4±11.6/7.7 mm Hg). aABP exceeded CBP by >10 mm Hg much more frequently than CBP exceeded aABP. The difference (aABP>CBP) was most pronounced in young adults and those with normal body mass index. The systolic difference progressively diminished, but did not disappear, at older ages and higher body mass indexes. The diastolic difference vanished around age 65 and reversed (CBP>aABP) for body mass index >32.5 kg/m 2 . Whereas 5.3% of participants were hypertensive by CBP, 19.2% were hypertensive by aABP; 15.7% of those with nonelevated CBP had masked hypertension. Conclusions: Contrary to a widely held belief, based primarily on cohort studies of patients with elevated CBP, ABP is not usually lower than CBP, at least not among healthy, employed individuals. Furthermore, a substantial proportion of otherwise healthy individuals with nonelevated CBP have masked hypertension. Demonstrated CBP−aABP gradients, if confirmed in representative samples (eg, NHANES [National Health and Nutrition Examination Survey]), could provide guidance for primary care physicians as to when, for a given CBP, 24-hour ABP would be useful to identify or rule out masked hypertension. Abstract : Supplemental Digital Content is available in the text.